New combinations in Struthiopteris spicant for the European flora - Wasowicz, Pawel; Galan, Jose Maria Gabriel Y; Perez, Ruben Pino (Phytotaxa, 2017)
Delimitation of genera in Blechnaceae Newman (1844: 8), a subcosmopolitan fern family with ca. 250 species, has remained uncertain for a long time. During the last decade, evidence has been accumulating about the polyphyletism within Blechnum Linnaeus (1753: 1077) (e.g. Shepherd et al. 2007, Rothfels et al. 2012, Gabriel y Galán et al. 2013, Perrie et al. 2014). Recent molecular studies (Gasper et al. 2016a) lead to an updated classification attempting to put morphological characters into a natural, phylogenetic relation (Gasper et al. 2016b). Because of these changes, the species most people associate with the genus Blechnum, B. spicant (Linnaeus 1753: 1066) Roth (1794: 56), is now treated under Struthiopteris Scopoli (1754: 25).